Nephrogenic hypertension due to intrasinusal renal artery branch aneurysm: surgical treatment by clipping - Danza, Rómulo; Arias, José; Tognola, Luis; Pravia, Juan A (Cirugía del Uruguay, 1975)
Case report of an aneurysm of an intrasinusal branch of the right renal artery, in a 44 year old female patient, suffering from severe arterial hypertension probably due to renovascular mechanism. This was a sacular aneurysm, 7 mm in diameter, which was satisfactorily solved by means of a method which we have not seen published, that is, clipping his neck employing Scoville clips far intracranial aneurysms. This permitted keeping complete intraparenchymatous renal circulation, as shown in selective postoperative angiography. The patient was relieved of her hypertension and fourteen months after the operation, arterial tension remained within normal limits.